Enabling Mg‐Based Ionic Liquid Electrolytes for Hybrid Dual‐Ion Capacitors. Issue 3 (10th December 2020) - Meister, Paul; Küpers, Verena; Kolek, Martin; Kasnatscheew, Johannes; Pohlmann, Sebastian; Winter, Martin; Placke, Tobias
Abstract: We report on the reversible (de)intercalation of TFSI − anions from a Mg‐based ionic liquid electrolyte, Mg(TFSI)2 in Pyr14 TFSI, in graphite ∥ activated carbon hybrid dual‐ion capacitor (DIC) cells. The role of different pseudo reference electrodes (PREs) including Ag‐wire and Li metal is discussed regarding the comparability of different battery cells. We show that an Ag‐wire PRE is not suitable for the designated purpose, while the use of a Li metal PRE results in high reproducibility. Mg‐based DIC cells are compared with cells based on pure Pyr14 TFSI and LiTFSI‐Pyr14 TFSI electrolytes, and with graphite ∥ Li metal dual‐ion cells employing LiTFSI‐Pyr14 TFSI. At 5.2 V vs . Li|Li +, Mg‐containing DIC cells reveal an improved performance compared to Li‐based cells, i. e ., higher capacity (87 vs . 85 mAh g −1 ) and higher Coulombic efficiency (98 vs . 96 %). These results may pave the way to further studies and performance improvements of Mg‐based batteries and to hybrid DIC chemistries with other cations, especially multi‐valent ones. Abstract : Towards low‐cost energy storage based on Mg electrolytes : The development of a hybrid dual‐ion capacitor using a Mg‐based ionic liquid electrolyte is presented. New insights into the performance of graphite ∥ activated carbon cells based on a Mg(TFSI)2 ‐Pyr14 TFSI electrolyte are reported and confirm improved specific capacity and Coulombic efficiency. This study can pave the way for further advancements in terms of suitable cell setups and improvements of Mg‐based storage devices including dual‐ion capacitors, dual‐ion batteries, or dual‐ion hybrid technologies.